Perkembangan Ekonomi Syariah Dalam Jual Beli Di Rawamangun Jakarta Timur - Anida Nur Fajri; Madian Muhammad Muchlis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sharia economics is an economic system based on the principles of Islamic law or sharia. These sharia principles cover many aspects such as peace, contentment and satisfaction with Islamic teachings. In the context of sharia economics, buying and selling transactions must be in accordance with Islamic principles and involve moral and ethical aspects. The aim of this research is to find out how important it is and how much people understand Islamic economics. It is equally known that many people have opinions or think that Islamic economics is wrong, and has many principles, etc. This research used a qualitative descriptive method, and data collection was carried out by direct observation and interviews with several sellers there. So the results of this research are that around 90% of sellers in the Rawamangun area use sharia economics in buying and selling transactions, on average they use sharia economic principles from the first time they trade, because according to them by using sharia economic principles, transactions buying and selling becomes fairer and better.